ANALYSIS OF SPEECH EVENTS IN DEDDY CORBUZIER'S CLOSE THE DOOR PODCAST, "WHY DO YOU PRAY ON SOCIAL MEDIA? BLOG! SINCE WHEN DOES GOD READ SOCIAL MEDIA!!," USING HYMES SPEAKING MODEL - Yayu Heryatun; Dini Fitriani; Rina Fitriana (Jurnal Riset Komunikasi, 2023)
This research discusses the analysis of speech events that occurred in Deddy Corbuzier's Close the Door podcast entitled, "How come you pray on social media?! Blog! Since when does God read social media!!” In this episode, the resource person presented by Deddy is a quite well-known cleric, namely Ustadz Das'ad Latif. This research uses qualitative methods with this episode broadcast as research data. The theory used to analyze the data is the speech events theory, SPEAKING model, from Hymes (1980). The research results show that podcasts are included in speech events because they contain supporting elements of speech in the form of setting, participant, end, act sequence, key, instrumentalities, norms of interaction and interpretation and genre.